Differential Gemcitabine Sensitivity in Primary Human Pancreatic Cancer Cells and Paired Stellate Cells Is Driven by Heterogenous Drug Uptake and Processing - Amrutkar, Manoj (Cancers (Basel), 2020)
SIMPLE SUMMARY: Pancreatic ductal adenocarcinoma (PDAC, also known as pancreatic cancer) is one of the deadliest tumor types, characterized by poor prognosis, profound chemoresistance and overall low survival. Gemcitabine remains the standard of care for all stages of PDAC, however, with poor clinical benefits which is considered to be due to reduced drug availability in tumor cells. Gemcitabine-induced cytotoxicity depends upon sufficient drug uptake followed by intracellular activation. Pancreatic stellate cells (PSCs), a major stromal component of PDAC, were recently reported to scavenge active metabolites of gemcitabine, thereby making it unavailable for cancer cells. Gemcitabine uptake and processing in both tumor cells and PSCs, as well as expression analysis of its molecular metabolic regulators, was investigated in this study. We observed heterogeneous gemcitabine-induced cytotoxicity in different pancreatic cancer cells whereas it was absent in PSCs. The gemcitabine-induced cytotoxicity in pancreatic cancer cells was driven by differential expression of its molecular regulators. ABSTRACT: Gemcitabine resistance in pancreatic ductal adenocarcinoma (PDAC) is attributed to cancer cell-intrinsic drug processing and the impact of the tumor microenvironment, especially pancreatic stellate cells (PSCs). This study uses human PDAC-derived paired primary cancer cells (PCCs) and PSCs from four different tumors, and the PDAC cell lines BxPC-3, Mia PaCa-2, and Panc-1, to assess the fate of gemcitabine by measuring its cellular uptake, cytotoxicity, and LC-MS/MS-based metabolite analysis. Expression analysis and siRNA-mediated knockdown of key regulators of gemcitabine (hENT1, CDA, DCK, NT5C1A) was performed. Compared to PSCs, both the paired primary PCCs and cancer cell lines showed gemcitabine-induced dose-dependent cytotoxicity, high uptake, as well as high and variable intracellular levels of gemcitabine metabolites. PSCs were gemcitabine-resistant and demonstrated significantly lower drug uptake, which was not influenced by co-culturing with their paired PCCs. Expression of key gemcitabine regulators was variable, but overall strong in the cancer cells and significantly lower or undetectable in PSCs. In cancer cells, hENT1 inhibition significantly downregulated gemcitabine uptake and cytotoxicity, whereas DCK knockdown reduced cytotoxicity. In conclusion, heterogeneity in gemcitabine processing among different pancreatic cancer cells and stellate cells results from the differential expression of molecular regulators which determines the effect of gemcitabine.